2015
DOI: 10.3389/fnbeh.2015.00166
|View full text |Cite
|
Sign up to set email alerts
|

Medial septum regulates the hippocampal spatial representation

Abstract: The hippocampal circuitry undergoes attentional modulation by the cholinergic medial septum. However, it is unclear how septal activation regulates the spatial properties of hippocampal neurons. We investigated here what is the functional effect of selective-cholinergic and non-selective septal stimulation on septo-hippocampal system. We show for the first time selective activation of cholinergic cells and their differential network effect in medial septum of freely-behaving transgenic rats. Our data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 73 publications
4
77
0
Order By: Relevance
“…Cholinergic neuron activation can trigger the septohippocampal system during inactive behavioral states, whereas non-cholinergic septal cell activation regulates hippocampal function during explorative behavior (active states). Cholinergic neuron activity is, thus, necessary for the transition from inactive to active hippocampal-related behavior, but is inefficient in inducing significant change in the activity of the hippocampal neurons during arousal states (Mamad et al 2015). Moreover, optogenetic activation of septal cholinergic neurons increases hippocampal activity within the theta band (2-6 Hz) in anesthetized mice (Vandecasteele et al 2014), and exploratory tasks have been reported to increase AchC in hipoccampus (Roland et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic neuron activation can trigger the septohippocampal system during inactive behavioral states, whereas non-cholinergic septal cell activation regulates hippocampal function during explorative behavior (active states). Cholinergic neuron activity is, thus, necessary for the transition from inactive to active hippocampal-related behavior, but is inefficient in inducing significant change in the activity of the hippocampal neurons during arousal states (Mamad et al 2015). Moreover, optogenetic activation of septal cholinergic neurons increases hippocampal activity within the theta band (2-6 Hz) in anesthetized mice (Vandecasteele et al 2014), and exploratory tasks have been reported to increase AchC in hipoccampus (Roland et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…, ; Mamad et al. ; Tsanov ; Gangadharan et al. ) that ultimately provides the temporal framework for the coordinated suppression or facilitation of synaptic inputs (Csicsvari et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Mamad et al. ) demonstrate the potential of this approach to serve as both a powerful tool for addressing fundamental basic science questions regarding the role of theta in learning and memory (Buzsaki ; Hasselmo ) and function as a neuroprosthetic that generates artificial oscillations in those with learning and memory difficulties. However, before researchers can address these possible uses of novel technology, there are two critical obstacles that must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the medial septal area provides most of the cholinergic innervation of the hippocampus (Jakab and Septum, 1995; Mamad et al, 2015). …”
Section: Discussionmentioning
confidence: 99%